Influence of the calcination process in traditional gypsum with structural behavior - Bel-Anzué, Pedro; Almagro, Antonio; Sáez Pérez, María Paz; Rodriguez-Navarro, Carlos (Ge-conservacion, 2017)
Gypsum is used as a finishing material with a principal aesthetical purpose. It is assumed that this binder has a poor structural behavior. However, it is also found as a structural material in many ancient constructions. In Spain there are several examples of architectural heritage with structures, floors and façades made of pure gypsum. In the studied area (Teruel), traditional gypsum represents the main material used in its architectural heritage. Nowadays, commercial gypsum is being used in restorations, but the different behavior between current and traditional gypsum results in non-compatible restorations. Here, we analyze the traditional gypsum calcination process by building two traditional ovens, assisted by locals masons, and we study how the differences in the calcination procedure can generate different gypsum products, which can be used either as a finishing material or as a structural material with a high mechanical resistance.